Optimization of Caffeic Acid Extraction from Dendropanax morbifera Leaves Using Response Surface Methodology and Determination of Polyphenols and Antioxidant Properties - Ming Zhang (MDPI AG, 2021)
The aim of this study was to optimize the extraction method for caffeic acid from the leaves of Dendropanax morbifera using response surface methodology (RSM), and subsequently determine the polyphenolic content and antioxidant capacity of the D. morbifera leaves extracts. The extraction process considered operating variables such as solvent concentration, extraction temperature, and extraction time, which were optimized via Box–Behnken experimental design. In addition, the antioxidant capacity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The optimal extraction conditions of 41.23% (v/v) methanol concentration, at 88.61 °C, and 1.86 h produced a maximum caffeic acid (CA) yield of 20.35 mg/g. Additionally, total polyphenols, total tannins, and total flavonoids contents in the leaves extracts of D. morbifera were 32.48 ± 2.05 mg GAE (gallic acid equivalents)/g, 17.61 ± 2.61 mg GAE/g, and 9.14 ± 0.17 mg QE (quercetin equivalents)/g, respectively. The results showed that methanol extracts exhibited an IC50 of approximately 14.3 mg AAE (ascorbic acid equivalent)/g. The results suggested that the extracts of D. morbifera leaves contain potential antioxidant activity, and could be a good source of functional food and used in medicinal applications.